2017
DOI: 10.5617/jeb.4443
|View full text |Cite
|
Sign up to set email alerts
|

A system to monitor segmental intracellular, interstitial, and intravascular volume and circulatory changes during acute hemodialysis

Abstract: This paper describes a new combined impedance plethysmographic (IPG) and electrical bioimpedance spectroscopic (BIS) instrument and software that allows noninvasive real-time measurement of segmental blood flow and changes in intracellular, interstitial, and intravascular volumes during various fluid management procedures. The impedance device can be operated either as a fixed frequency IPG for the quantification of segmental blood flow and hemodynamics or as a multi-frequency BIS for the recording of intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The Ri and Re values are then used to compute the intracellular and extracellular compartment volumes of the calf during the simulated hemorrhage. The extracellular volumes is then used to calculate [ 10 ] the intravascular and interstitial volumes of the calf. The intravascular (nVblood), intracellular (nVcellular) and interstitial (nVinterstitial) compartment volumes are shown, normalized to the mean of control, in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ri and Re values are then used to compute the intracellular and extracellular compartment volumes of the calf during the simulated hemorrhage. The extracellular volumes is then used to calculate [ 10 ] the intravascular and interstitial volumes of the calf. The intravascular (nVblood), intracellular (nVcellular) and interstitial (nVinterstitial) compartment volumes are shown, normalized to the mean of control, in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently electrical bioimpedance spectroscopy (BIS) was validated [ 8 ] and used [ 9 , 10 ] to monitor fluid shifts between the intracellular, interstitial and intravascular compartments during dialysis. The ZSpec-2, (UFI Inc., Morro Bay, CA) combines two bioimpedance instruments into a single device.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed descriptions of the EIS and analytical procedures used in this study can be found in Sasser and Gerth [3], Gerth and Watke [4] and Fricke [5,6]. The EIS was previously validated [7] and used [8,9] to monitor fluid shifts between the intracellular, interstitial, and intravascular compartments during dialysis.…”
Section: Bioimpedancementioning
confidence: 99%
“…However, our proprietary software was then used to divide the extracellular compartment volume into its intravascular and interstitial components. The electrical bioimpedance spectrographic mode was validated [ 25 ] and used [ 26 , 27 ] to monitor fluid shifts between the intracellular, interstitial, and intravascular compartments during dialysis. This instrumentation was used in this study to monitor relative changes in interstitial and intravascular compartment volumes during simulated hemorrhage and the use of PEEP [ 28 ].…”
Section: Introductionmentioning
confidence: 99%